ACE2 diversity in placental mammals reveals the evolutionary strategy of SARS-CoV-2 - Bibiana S.O. Fam; Pedro Vargas-Pinilla; Carlos Eduardo G. Amorim; Vinicius A. Sortica; Maria Cátira Bortolini (Genetics and Molecular Biology)
Abstract The recent emergence of SARS-CoV-2 is responsible for the current pandemic of COVID-19, which uses the human membrane protein ACE2 as a gateway to host-cell infection. We performed a comparative genomic analysis of 70 ACE2 placental mammal orthologues to identify variations and contribute to the understanding of evolutionary dynamics behind this successful adaptation to infect humans. Our results reveal that 4% of the ACE2 sites are under positive selection, all located in the catalytic domain, suggesting possibly taxon-specific adaptations related to the ACE2 function, such as cardiovascular physiology. Considering all variable sites, we selected 30 of them located at the critical ACE2 binding sites to the SARS-CoV-like viruses for analysis in more detail. Our results reveal a relatively high diversity of ACE2 between placental mammal species, while showing no polymorphism within human populations, at least considering the 30 inter-species variable sites. A perfect scenario for natural selection favored this opportunistic new coronavirus in its trajectory of infecting humans. We suggest that SARS-CoV-2 became a specialist coronavirus for human hosts. Differences in the rate of infection and mortality could be related to the innate immune responses, other unknown genetic factors, as well as non-biological factors.